دراسة إحصائية تحليلية للمحتوى الترجمي في مجلة معالم: Statistical and analytical study of translation content In Maalem magazine - BenIssa , Mahdia; Benmalek , asma (Maalim, 2025)
Since its establishment, the High Council of the Arabic Language has strived to develop a comprehensive strategy for translation in Algeria. This has been achieved through a series of initiatives, including the translation of guides into Arabic across various fields to serve the national community. The council has also contributed to the creation of functional, bilingual, or trilingual guides for specific ministries. Furthermore, it has actively promoted rigorous scientific publishing through the 'Maalim for Translation' journal and organized academic conferences addressing translation and its related issues. These conferences have provided a platform for academics and translation experts to discuss a range of concerns, such as the conditions for revitalizing translation in Algeria, the relationship between the Arabic language and translation, and the role of translation as a bridge between languages. In this research, we have conducted and presented an applied study of the translated content in the 'Maalim' journal from its inception until 2023.